Is there a diversification “cost” of shari’ah compliance? empirical evidence from Malaysian equities - Mustaffa Kamil, Nazrol Kamil; Bacha, Obiyathulla Ismath; Masih, Mansur (2014)
Islamic equity portfolios work with a smaller investment universe given the filtering of non-Shari’ah compliant stocks. It has been theoretically argued that this culminates in suboptimal portfolio diversification which in turn adversely affects risk-adjusted returns. We employ a number of methods, namely construction of efficient frontiers, time-varying maximum Sharpe ratios, MGARCH-DCC and analysis of covariance (ANCOVA), to offer empirical evidence that such a conceived portfolio diversification “penalty” is far from a foregone conclusion, at least empirically. Our results show that Islamic portfolios are not invariably handicapped in terms of portfolio diversification. We also explored dimensions which may account for differences in relative investment performance between Islamic and conventional portfolios such as portfolio constraints, length of investment horizon and market conditions. We believe this paper is among the first to apply substantial empirical analysis of the portfolio diversification perspective on Islamic equity investments.